Identifying anti-trust markets - Paul A. Geroski; Rachel Griffith (Institute for Fiscal Studies (IFS), 2003)
The identification of markets is a standard feature of anti-trust investigations, and the substantive decision in many cases stands or falls on the precise market definition selected.Market shares are often used to help establish jurisdiction or, more generally, to sort out priorities for anti-trust agencies. Market shares are also sometimes used as an observable measure of market power, meaning that the fact of finding high market shares is sometimes taken to be tantamount to uncovering the existence of market power.
Keywords: 330; Relevanter Markt; Konzentrationspolitik; Wettbewerbsbeschränkung; Marktanteil; Wettbewerbstheorie